Ethnobotanical Study of Medicinal Plants in Karangwangi, District of Cianjur, West Java - Desak Made Malini; Madihah Madihah; Joko Kusmoro; Fitri Kamilawati; Johan Iskandar (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2017)
The knowledge and usage of plant as medicinal remedy by current generation are not as extensive as previous; therefore, many rural communities with restricted modern medical access still rely on traditional medicine. This paper provides significant ethnobotanical information on medicinal plants in Karangwangi Village of Cianjur District, West Java Indonesia. This study aimed to identify plants collected for medical purposes by the local people as well as to document the local names, uses, preparation, and location of these plants. Ethno botanical data was recorded by opting people participation and key informant approach involving semi-structured interviews, group discussions and filling of questionnaires. The results showed a total of 114 medicinal plants belonging to 50 families were identified. Zingiberaceae was the most-frequently cited (nine species), followed by Asteraceae, Euphorbiaceae, and Fabaceae (seven species each). The most-used plant parts were leaves (51.8%), followed by stems (22.9%) and the most common preparations were decoction, poultice and squeezed. Most of the plants were obtained from the house-yard and total of 30 medicinal uses were recorded. The ethnobotanical result documented in this study showed that this area is rich in medicinal plants and these plants are still commonly used for medicinal purposes among the people in their daily lives. Ethnobotanical heritage should be preserved, however, there is a gradual loss of traditional knowledge about these plants in new generation. Further, the findings can be used as baseline information for further scientific investigation for analyzing phytochemical, pharmaceutical and other biological activities for future drug discovery.